Permissive untreated pseudoaneurysm concept in damage control interventional radiology for traumatic pancreaticoduodenal artery injury - Takafumi Yonemitsu; Naoaki Shibata; Nozomu Shima; Junya Fuchigami; Yuichi Miyake; Akira Ikoma; Hiroki Minamiguchi; Tetsuo Sonomura; Seiya Kato (Acute Medicine & Surgery, 2023)
Background Angioembolization for traumatic pancreaticoduodenal artery injury with unstable circulation, which characteristically requires a prolonged procedure time, does not yet have a standardized strategy for damage control interventional radiology. Case Presentation We encountered two cases of rare traumatic pancreaticoduodenal artery injury wherein the patients were saved by a multidisciplinary team with a shared goal of clinical success, rather than the procedural success of angioembolization. Both patients treated with angioembolization had residual pseudoaneurysm or faint extravasation in the pancreaticoduodenal artery arcade. We prioritized critical care with preemptive plasma transfusion and aggressive blood pressure control, and planned repeat angiography. The patients showed no clinical signs of rebleeding or pseudoaneurysm based on computed tomography during follow‐up. Conclusion Our findings suggest that the permissive untreated pseudoaneurysm concept can be useful in developing damage control interventional radiology strategies for trauma cases with challenging time limitations, such as traumatic pancreaticoduodenal artery injury with circulatory collapse.